MODEL PEMBELAJARAN MENGGIRING SEPAKBOLA PADA SISWA SEKOLAH MENENGAH PERTAMA - Jetra Viktoria (Ensiklopedia of Journal, 2019)
The purphose of research and development is to produce a model of the dribble skill junior high school. In addition, research and development is carried out to obtain in-depth information on: the development and application of model of the dribble skill junior high school Basic and examine the effectiveness, efficiency and attractiveness of the model created child. Research and development of this method development Research Research& Development (R & D) from Borg and gall. The subjects in research and development are junior high school students consisting of 30children. Instruments used in research and development are the questionnaire, questionnaires, as well as a dribble skill test that is used to collect the data rate of the dribble skill of junior high school, while the stages in the research and development is, at this stage: (1) analysis needs, (2) expert evaluation (initial product evaluation); (3) small group limited (small group testing); and (4) the main trial (field testing). Test the effectiveness of the model using the dribble skill test to determine the level of the dribble skill before giving treatments in the form of models developed dribble and to determine the dribble skill level of junior high school children after treatment or treatments that balance model to development. From the initial tests conducted by the students obtained the degree of dribble in 1584, then after a given treatment in the form of dribble models of junior high school age students obtained the dribble skill of 1381. Thus dribble model effective at junior high school age to improve the dribble skill of junior high school age. Based on the results of the development can be concluded that: (1) the dribble junior high school age models can be developed and applied in Physical Education and improve dribble skill. (2) The dribble of junior high school age models that have been developed, data showed the effectiveness and development results dribble models of junior high school.